HLA class I-mediated stress fiber formation requires ERK1/2 activation in the absence of an increase in intracellular Ca(2+) in human aortic endothelial cells - Ziegler, Mary E. (American Physiological Society, 2012)
Following transplantation, HLA class I antibodies targeting donor endothelium stimulate cell proliferation and migration, which contribute to the development of transplant vasculopathy and chronic allograft rejection. Dynamic remodeling of the actin cytoskeleton regulates cell proliferation and migration in endothelial cells (ECs), but the mechanism(s) involved remain incompletely understood. We explored anti-HLA class I antibody-mediated alterations of the cytoskeleton in human aortic ECs (HAECs) and contrasted these findings to thrombin-induced cytoskeleton remodeling. Our results identify two different signaling pathways leading to myosin light chain (MLC) phosphorylation in HAECs. Stimulation of HAECs with thrombin at 1 U/ml induced a robust elevation of intracellular Ca(2+) concentration, increased MLC phosphorylation, and promoted stress fiber formation via MLC kinase (MLCK) and Rho kinase (ROK) in an ERK-independent manner. In contrast, HAECs stimulated with HLA class I antibodies did not promote any detectable change in intracellular Ca(2+) concentration but instead induced MLC phosphorylation and stress fiber assembly via MLCK and ROK in an ERK1/2-dependent manner. Stimulation of HAECs with low-dose thrombin (1 mU/ml) induced signaling cascades that were similar to stimulation with HLA class I antibodies. HLA class I antibodies also stimulated the translocation of mammalian target of rapamycin complex 2 (mTORC2) and ERK1/2 from the cytoplasm to the plasma membrane independently of stress fiber assembly. These findings identify novel roles for HLA class I signaling in ECs and provide new insights into the role of ERK1/2 and mTORC2 in cytoskeleton regulation, which may be important in promoting transplant vasculopathy, tumor angiogenesis, and atherosclerosis.